The Apocalypse of The Morning Star: Science fiction, judgment day and Karl Ove Knausgård - Andersen Kraglund, Rikke (Nordlit, 2022)
This article examines narrative aspects of Karl Ove Knausgaard’s The Morning Star (2020) with a special interest in the novel’s supernatural and apocalyptic elements. At the publication of the book, it was discussed whether the supernatural events in the novel should be explained based on real-world frames and pre-existing cognitive parameters or more fantastical (NRK 2020). Within the framework of unnatural narratology, I want to emphasize that the narratives can go beyond imaginable real-world situations and a mimetic explanation may miss something crucial about the narrative when treating the unnatural as hallucinations or dreams.
Keywords: Karl Ove Knausgård; The Morning Star; science fiction; apocalypse; unnatural narratology